Intraplate Late Jurassic deformation and exhumation in western central Argentina: Constraints from surface data and U–Pb detrital zircon ages - Naipauer, Maximiliano (2012)
Intraplate deformation has been described in several tectonic settings and recently in western central Argentina it has been proposed to explain the complex structural patterns developed between Early Jurassic and Cretaceous times along the Huincul deformation zone. We integrate new field data and detrital zircon ages of the exposed portion of the Huincul High that permit us to quantify the significance of this intraplate deformation in the relief generation. A stratigraphic and structural record of a Jurassic pulsed contractional deformation is derived from field surveys. It is documented through multiple unconformities and growth geometries linked to NE and E-W oriented growth structures extensively developed across the studied region. The pattern of zircon ages from the analyzed Late Jurassic successions indicates that they have a clear provenance from sources located along the Huincul deformation zone. The Tordillo Formation outcrops north of the Huincul High have a dominant provenance from the Andean Jurassic arc; while the Quebrada del Sapo Formation, south of the Huincul High, has a significant input from Late Triassic (220-200. Ma) and Late Permian (280-260. Ma) sources of the axial exposures of the Huincul High. Surface data, combined with detrital zircon ages proved to be a powerful method to confirm the presence of an ancient positive element developed within the southern Neuquén basin. Its genesis falls within the early history of the Huincul deformation zone, where several structural features indicate pulses of growth since Early Jurassic times prior to the main Andean contractional cycle that started in the Late Cretaceous. Therefore, these data document for the first time the importance of the early contractional phases in the relief construction in the southern Central Andes, reinforcing previous hypotheses about pre-Andean intraplate deformation concentrated along this extensive east-west oriented basement weakness zone.